Arrowheads in the cultural-historical property repository of the Administration of Cultural Heritage of Kerman. An Introduction - KHONSARINEJAD, Ehsan; RIAHIYAN GOHORTI, Reza; TAVAKOLI, Sahar (Historia i Świat, 2023)
In this paper, the authors have examined 94 unprovenanced arrowheads (tanged and socketed) that are stored in the cultural historical property repository of the Administration of Cultural Heritage of Kerman Province (Southeastern Iran). The illlegal possessors claimed to have discovered the arrowheads via illegal diggings in the Kerman Province. Most of the examined arrowheads were probably designed for warfare and are comparable to findings within current borders of Iran or its vicinity. Most of the tanged arrowheads probably date to the Iron Age of Iran (1450-550 B.C.). Most of the trilobate arrowheads can be compared to the findings of Achaemenid sites or resemble items that have been excavated from layers associated with the Achaemenids. Some of the Bronze Age arrowheads, however, could not be compared with any items that have been recovered from Iran or its neighboring regions.